PENGARUH KOMITMEN ORGANISASI, BUDAYA PERUSAHAAN, SELF EFFICACY TERHADAP KINERJA KARYAWAN PADA PT. DUTA INTIKA GIANYAR - Damayanti, Ni; Putri, Cokorda (Fakultas Ekonomi dan Bisnis Universitas Pasundan, 2024)
Company sustainability occurs not only because it maintains the quality of goods but also requires quality resources. If employees have high commitment to the company, good performance will be achieved. Not only commitment, company culture also has an influence on employee performance. If a company or organization has a great culture, it can create good performance for a long time. Employees are not only influenced by commitment and culture but are also influenced by self-efficacy. Employees who carry out their duties with great self-efficacy means they have a sense of confidence and self-confidence in their own abilities. The purpose of this research is so that we can see the simultaneous and partial influence of Organizational Commitment, Company Culture, and Self-Efficacy on Employee Performance. This research was conducted for PT. Duta Intika Gianyar is located at Jl. Bypas Dharma Giri No. 888 New Temple Neighborhood Gianyar. The sample in this study was all employees at PT. Gianyar Intika Ambassador. The population of this research is all employees at PT. There are a total of 31 Intitika Gianyar ambassadors. The type of analysis applied in this method is quantitative research. This sample determination procedure applies a saturated sampling method and an information analysis system implemented, namely observation, direct question and answer, and questionnaires. This research observation states that Organizational Commitment produces an absolute and important impact on Employee Performance. Company culture also has an absolute and important impact on employee performance. Self Efficacy has an absolute and important impact on employee performance. And Organizational Commitment, Company Culture, and Self-Efficacy partially have an absolute and important influence on Employee Performance.